Double guide double wrist 5F left coronary artery transradial percutaneous coronary intervention and the X-Kiss technique. (2nd July 2016) - Vincent, Dangoisse; Erwin, Schroëder; Hanet, Claude; Guédès, Antoine; Samir, Pancholy
ABSTRACT: Percutaneous coronary intervention for bifurcated anatomy, particularly at the proximal left coronary artery site, requires guide catheters (GC) of at least 6 french and preferably larger in diameter. We describe a new trans-radial approach more suitable for small artery size: the simultaneous use of both radial arteries for double cannulation of the LMCA with 5F GC: each GC will target either the LM/LAD or the LM/CX artery (or LM-LAD/LM-LAD-1st diagonal branch) stenoses. The technique successfully was applied to 5 cases. When the technique was used for distal left main coronary artery stenoses (3 cases), a special crogss-like configuration obtained when guide catheters, coronary wires and balloons kissed was observed.